EVALUASI MANAJEMEN ALAT PELINDUNG DIRI (APD) DI INSTALASI LAUNDRY RS X - Yohana Riswa Dwiastuti; Suroto Suroto; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2017)
The hospital is one of the work places with a hazard variety that may cause health effects. One of the hospital workers contacts with the dangers that worker in high risk Laundry Installations. The use of PPE is one of the control measures that can be done and as a control efforts need a good management so that PPE is used in accordance with the potential dangers that exist and need in Laundry Installation. However, in RS XPPE management has not run optimally. Therefore, it needs to be evaluated to assess management PPE that has been implemented. This research purpose to give a description of evaluation management PPE in Laundry Installation RS X. Research method used is a qualitative description research with in-depth interviews with the subject of research of 6 people as a main informant and 2 people as a triangulation informant. The result of studies have shown an evaluation management PPE in the Laundry Installation RS X had never been done even though the application of PPE has been running in accordance with the procedure.RS X need to made identification of danger and the management of PPE systematically so that the availability of PPE is evenly and in accordance with the needs of the laundry installation